Arthropods associated with paraguay tea in Chapecó, SC - Chiaradia, Luís Antonio (Revista de Ciências Agroveterinárias, 2010)
Over a hundred species of mites and phytophagous insects infests paraguay tea trees, Ilex paraguariensis Saint Hil. (Aquifoliaceae). In order to quantify these species, a faunal survey was conducted in an orchard located in Chapecó, Santa Catarina State, Brazil. Sampling was performed biweekly from July 2003 to June 2006 using a vacuum equipment (D-vac). The collected arthropods were separated at the laboratory, the results were organized by date and taxon, from class to species. 10,556 specimens were captured, including 4,262 pests; 4,236 natural enemies and 2,058 arthropods with other habits. Caterpillars, aphids, leafhoppers and bugs were the most pests colleted. Spiders, microhymenoptera and ladybugs were predominat among natural enemies. Ants and cockroaches prevailed among the arthropods with other habits.